The Influence of Principal Competency on Work Motivation and Its Impact on School Climate in Junior High Schools in Cawas District, Klaten Regency - Annisa Dewi Permatasari; Cepi Safruddin Abdul Jabar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze the influence of principal competencies which include decision-making, communication, and the ability to motivate teachers' work motivation and its impact on the school climate. A quantitative approach was used with a path analysis design. The population consisted of public and private junior high school teachers in Cawas District, Klaten Regency. A total of 125 teachers were selected using proportional random sampling. The instrument was developed using a Likert scale and tested for validity and reliability through Confirmatory Factor Analysis (CFA) and Construct Reliability (CR). The results show that decision-making and the ability to motivate have a significant positive effect on work motivation, whereas communication does not. Work motivation was found to significantly influence school climate and mediate the effects of decision-making and motivational ability on the school climate.